(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
This study investigates the prevalence of distrust in traditional news media among residents of Cross River State, Nigeria, exploring its demographic correlates and underlying factors. Utilizing a cross-sectional survey design, primary data were collected from 384 participants across urban and rural communities using stratified random sampling. Findings reveal a significant level of distrust, with 62.5% of respondents expressing skepticism toward traditional media due to perceived bias, sensationalism, and political influence. Younger respondents (18–35 years) and those with higher education exhibited greater distrust, while urban residents reported slightly higher skepticism than rural counterparts. The study is grounded in the Media Dependency Theory, which posits that reliance on media shapes perceptions of credibility. Results highlight the growing influence of social media as an alternative information source, exacerbating distrust in traditional outlets. Recommendations include enhancing media transparency, fostering community engagement, and promoting media literacy to rebuild trust. This study contributes to understanding media distrust in a developing context, with implications for journalism and democratic processes in Nigeria.